1970
DOI: 10.1901/jaba.1970.3-213
|View full text |Cite
|
Sign up to set email alerts
|

OPERANT LEARNING PRINCIPLES APPLIED TO TEACHING INTRODUCTORY STATISTICS1

Abstract: The present experiment sought to develop a practical and effective method for teaching the beginning elements of hand-writing in a Head Start program. The method consisted of reinforcing responses to a writing program by giving the children access to a variety of activities normally available in the pre-school classroom. Tokens were presented for correct responses. The children then used the tokens to select reinforcers, such as snacks and access to a variety of play activities. In an experimental evaluation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
30
0

Year Published

1973
1973
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 7 publications
0
30
0
Order By: Relevance
“…Early studies found that teacher attention could be altered to provide an immediate and natural system for changing on-task rates (Chadwick and Day, 1971;Hall et al, 1968;Hasazi and Hasazi, 1972;Ward and Baker, 1968). However, attention was not always effective as a reinforcer, 5Brigham, Finfrock, Breunig, and Bushell, 1972;Chadwick and Day, 1971;Hall and Broden, 1967;Harris and Sherman, 1973;Hasazi and Hasazi, 1972;Hopkins, Schutte, and Garton, 1971;Jacobson, Bushell, and Risley, 1969;Knapczyk and Livingston, 1973;Lahey, McNees, and Brown, 1973;Martin, England, Kaprowy, Kilgour, and Pilek, 1968;Miller and Schneider, 1970;Salzberg, Wheeler, Devar, and Hopkins, 1971; Wolk, Giles, and and token systems with more potent backups became popular alternatives (O'Leary and Becker, 1967, p. 637;Quay, Werry, McQueen, and Sprague, 1966). Studies that dealt with token systems typically dropped the analysis of adult attention and emphasized instead the effect of nonsocial consequences on appropriate classroom behavior.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Early studies found that teacher attention could be altered to provide an immediate and natural system for changing on-task rates (Chadwick and Day, 1971;Hall et al, 1968;Hasazi and Hasazi, 1972;Ward and Baker, 1968). However, attention was not always effective as a reinforcer, 5Brigham, Finfrock, Breunig, and Bushell, 1972;Chadwick and Day, 1971;Hall and Broden, 1967;Harris and Sherman, 1973;Hasazi and Hasazi, 1972;Hopkins, Schutte, and Garton, 1971;Jacobson, Bushell, and Risley, 1969;Knapczyk and Livingston, 1973;Lahey, McNees, and Brown, 1973;Martin, England, Kaprowy, Kilgour, and Pilek, 1968;Miller and Schneider, 1970;Salzberg, Wheeler, Devar, and Hopkins, 1971; Wolk, Giles, and and token systems with more potent backups became popular alternatives (O'Leary and Becker, 1967, p. 637;Quay, Werry, McQueen, and Sprague, 1966). Studies that dealt with token systems typically dropped the analysis of adult attention and emphasized instead the effect of nonsocial consequences on appropriate classroom behavior.…”
mentioning
confidence: 99%
“…Promptly, however, some researchers began examining the effect of another class of more-natural reinforcers-play activities and materials, and free time. These "natural" reinforcers were found in the home (Nordquist and Wahler, 1973;Phillips, 1968), in psychiatric institutions (Ayllon and Azrin, 1968;Mitchell and Stoffelmayr, 1973), and in educational settings for children and adolescents.6 It has been argued that natural reinforcers should be used whenever 6Betancourt and Zeiler, 1971;Brigham et al, 1972;Harris and Sherman, 1973;Hopkins et al, 1971;Jacobson et al, 1969;Knapczyk and Livingston, 1973;Miller and Schneider, 1970;Osborne, 1969;Reynolds and Risley, 1968;Salzberg et al, 1971;Wolf et al, 1968. possible because they should facilitate generalization of behavior change (Axelrod, 1971;Lovaas, Koegel, Simmons, and Long, 1973).…”
mentioning
confidence: 99%
“…Modelling can be useful to the child's acquisition of behaviors important to schooling (e.g., Lahey, 1971) and to socialization generally (Bandura, 1969;Bandura and Walters, 1963). Finally, contingencies of reinforcement have successfully enlarged the repertoires of academic behavior of both preschool (Miller and Schneider, 1970;Tawney, 1972) and older children (Brigham, Graubard, and Stans, 1972) in the classroom.…”
mentioning
confidence: 99%
“…A second matched group of six children received only verbal praise for correct responses to the same instructional materials and failed to improve in arithmetic but showed significant gains in language. Re-test scores one year later revealed that the Token Group maintained its gains in both subjects whereas the language performance of the No-Token Group showed a significant decline.Behavior modification research with children of normal intelligence (e.g., Haring, Hayden, and Nolen, 1969;Miller and Schneider, 1970;Chadwick and Day, 1971) has amply demonstrated the effectiveness of token economy systems in producing improvement when successful performance on academic subjects is selected as the "target behavior" for modification. There are few comparable studies with retarded children (e.g., Birnbrauer, Wolf, Kidder, and Tague, 1965).…”
mentioning
confidence: 99%
“…Behavior modification research with children of normal intelligence (e.g., Haring, Hayden, and Nolen, 1969;Miller and Schneider, 1970;Chadwick and Day, 1971) has amply demonstrated the effectiveness of token economy systems in producing improvement when successful performance on academic subjects is selected as the "target behavior" for modification. There are few comparable studies with retarded children (e.g., Birnbrauer, Wolf, Kidder, and Tague, 1965).…”
mentioning
confidence: 99%